Building States Without Society: European Union Enlargement and the Transfer of EU Social Policy to Poland and Hungary - Sissenich, Beate, (Lexington Books, 2007)
Focusing on the 2004 enlargement of the European Union, Building States without Society highlights the real limits of cross-national rule transfer even when power is uneven between rule-makers and rule-takers. Tracing the role of labor and other non-state actors in transferring rules, Beate Sissenich shows the persistent relevance of national politics, specifically state capacity and interest organizations. Social network analysis demonstrates that even in a highly integrated Europe, state borders continue to structure communications.